Evaluation of recalcitrant features impacting enzymatic saccharification of diverse agricultural residues treated by steam explosion and dilute acid1. Issue 75 (19th August 2015) - Gaur, Ruchi; Agrawal, Ruchi; Kumar, Rahul; Ramu, E.; Bansal, Veena Rani; Gupta, Ravi P.; Kumar, Ravindra; Tuli, Deepak K.; Das, Biswapriya
<x xml:space="preserve">Abstract</x> Exploring agricultural biomass for biofuel production necessitates pretreatment as a prerequisite step.